Profitabilitas Dan Leverage Dalam Mempengaruhi Effective Tax Rate - Kurniasari, Erni; Listiawati, Listiawati; Listiawati, Listiawati; Listiawati, Listiawati (Jurnal Manajemen, 2019)
This study aims to determine the influence of profitability and leverage on effective tax ratepartially and simultaneously. The variables used in this study are effective tax rate, profitability, and leverage. This study is an empirical study with sample selection based on criteria. The sample used was 8 pharmaceutical companies listed on the Indonesia Stock Exchange in the period 2013-2017. The results of the study prove that partially profitability has no influence on effective tax rate and leverage has an influence on effective tax rate. Simultaneously it is proven that profitability and leverage have an influence on effective tax rate. Based on the coefficient of determination, it can be interpreted that effective tax rate is influenced by profitability and leverage of 17.3% and other variables of 82.7%.